Health equity considerations in pragmatic trials in Alzheimer's and dementia disease: Results from a methodological review. Issue 1 (5th February 2023) - Nicholls, Stuart G.; Al‐Jaishi, Ahmed A.; Niznick, Harrison; Carroll, Kelly; Madani, Mohamad Tarek; Peak, Katherine D.; Madani, Leen; Nevins, Pascale; Adisso, Lionel; Li, Fan; Weijer, Charles; Mitchell, Susan L.; et al.
Abstract: Introduction: To improve dementia care delivery for persons across all backgrounds, it is imperative that health equity is integrated into pragmatic trials. Methods: We reviewed 62 pragmatic trials of people with dementia published 2014 to 2019. We assessed health equity in the objectives; design, conduct, analysis; and reporting using PROGRESS‐Plus which stands for Place of residence, Race/ethnicity, Occupation, Gender/sex, Religion, Education, Socioeconomic status, Social capital, and other factors such as age and disability. Results: Two (3.2%) trials incorporated equity considerations into their objectives; nine (14.5%) engaged with communities; 4 (6.5%) described steps to increase enrollment from equity‐relevant groups. Almost all trials (59, 95.2%) assessed baseline balance for at least one PROGRESS‐Plus characteristic, but only 10 (16.1%) presented subgroup analyses across such characteristics. Differential recruitment, attrition, implementation, adherence, and applicability across PROGRESS‐Plus were seldom discussed. Discussion: Ongoing and future pragmatic trials should more rigorously integrate equity considerations in their design, conduct, and reporting. Highlights: Few pragmatic trials are explicitly designed to inform equity‐relevant objectives. Few pragmatic trials take steps to increase enrollment from equity‐relevant groups. Disaggregated results across equity‐relevant groups are seldom reported. Adherence to existing tools (e.g., IMPACT Best Practices, CONSORT‐Equity) is key.